The spatiotemporal evolution of green development in western China under the main functional planning of national land space - Yubin Ma; Xiaoling Yuan; Haotian Chen; Xing Zhang; Yue Li; Hang Yin; Zhengda Li (Ecological Indicators)
A comprehensive and precise assessment of green development levels in China’s western region, guided by the main functions of national land space strategy, constitutes a fundamental prerequisite for reliably identifying key determinants of green development and systematically exploring viable pathways for its optimization. In this work, we construct an evaluation index system that includes three dimensions (production, ecology, and living), to accurately capture the regional characteristics of ecological, agricultural, and urban functional zones in the western region. We then use the dynamic comprehensive evaluation and spatial analysis methods to study the green development levels and the spatiotemporal evolution characteristics of these zones from 2006 to 2022. It is found that the green development levels of these zones exhibit an upward trend. And our results confirm that the improvement of green development in ecological functional zones is attributed to significant progress in production and ecology, and that of agricultural functional zones is dominated by the ecology, as well as that of urban functional zones is the result of the coordinated promotion of production, ecology, and living. Moreover, the comparison between cities further reveals that the green development levels between cities within the three functional zones are relatively concentrated, the advantages of green development level of higher-ranked cities are not obvious, and there is a significant gap in the level of green development between lower- and higher-ranked cities. In addition, the overall spatial distributions of green development levels in three zones exhibit a pattern of “higher in the south and lower in the north”, and the green development in each zone shows significant positive spatial correlation, which strengthens over time. In view of the development status and shortcomings of various functional zones in the western region, we put forward targeted policy suggestions, which can provide reference and follow for the further development of these functional zones.